Structures and properties of thermally conductive thermoplastic composites - Ng, Hsiao Yen. (2008)
Formulate thermoplastic composites that offer high thermal conductivity and good electrical insulating properties for electronic packaging purposes. Examine other important properties such as rheological properties (ease of processing) and the mechanical properties (end use performance).